Primary School Pre-Service Teachers' Perceptions of Effective Online Learning by Using LINE Application during Covid-19 Pandemic - Aprinastuti, Christiyanti (International Conference on Elementary Education, 2021)
The Covid-19 pandemic that has hit Indonesia since March 2020 suddenly forced learning from elementary to tertiary levels to be carried out online. The LINE application is a social media platform that has live features. This application is an alternative that is used as a means of emergency learning during the Covid-19 pandemic. This study aimed to describe the perceptions of Sanata Dharma University PGSD students on the effectiveness of online learning using the LINE application. The subjects of this study were 252 students. The method used is descriptive quantitative through online surveys. This study's results were the students' perceptions of using the LINE application on the effectiveness of learning showed that 73.4% of students received clear levels of information. As many as 67, 9% of students stated that they were ready to accept learning, as many as 71% of students were motivated, as many as 58.7% of students stated that they were effective in terms of time, 63.5% of students felt that the learning objectives were achieved, as many as 67.9% of students stated that the use of LINE was quite attractive and interactive, and 71% stated that the use of the LINE application was sufficient to support learning. Students also conveyed that the advantages of this application are saving on internet quota usage, while the weakness of this application is the absence of a recording feature. This research concludes that students' perceptions state that using the LINE application is effective for learning. 5% of students felt that the learning objectives were achieved, as many as 67.9% of students stated that the use of LINE was quite attractive and interactive, and as many as 71% stated that using the LINE application was sufficient to support learning. Students also conveyed that this application's advantages are saving on internet quota usage, while the weakness of this application is the absence of a recording feature.